Model Mediasi Adat dalam Penyelesaian Perkara Pelanggaran Hukum di Kabupaten Pelalawan - Dasrol Dasrol; Riska Fitriani (Jurnal Ilmiah Penegakan Hukum, 2022)
This article aims to discuss the condition of one area in Riau Province that is still implementing legal cases' settlement using customary law with the mediation method, namely Pelalawan Regency. The problem of this research is finding out how ninik mamak and traditional leaders are mediators in resolving legal cases in each sub-district or village in Pelalawan Regency. In order to approach this problem solving, a sociological legal research theory reference is used and then analyzed qualitatively. In collecting data, apart from interviews and literature studies, it is also obtained by involving local indigenous community leaders. This study indicates that ninik mamak or traditional leaders as representatives of indigenous peoples have an important role, namely as mediators and are obliged to resolve legal cases that occur in the community, especially in Pelalawan Regency. Therefore, it is hoped that this article can provide a new perspective for law enforcement officers in overcoming the many cases that cannot be resolved by the judicial subsystem and the overcapacity of correctional institutions throughout Indonesia